Cold magnetized quark matter at finite density in a nonlocal chiral quark model - Ferraris, Sebastián Alberto (2021)
We study the behavior of two-flavor dense quark matter under the influence of an external magnetic field in the framework of a nonlocal chiral quark model with separable interactions. The nonlocality is incorporated in the model by using a Gaussian form factor. It is found that for low and moderate values of magnetic field there is a decrease of the critical chiral restoration chemical potential µc, i.e. an inverse magnetic catalysis effect is observed. For larger values of eB the behavior of µc becomes more or less flat, depending on the parametrization. Within the considered parametrization range we do not find a significant growth of the critical chemical potential for large magnetic fields, as occurs in the case of the local NJL model.